Surgical Outcome of Open Lumbar Microdiscectomy in Lumbar Disc Herniation Patients - Thapa, Bishnu Babu; Baskota, Narendra; Shah, Rajesh Pratap (Nepal Orthopaedic Association Journal, 2019)
INTRODUCTION: Lumbar disc herniation is common medical problem. PIVD presented with intractable pain or severe neurological symptoms related to nerve root compression. The most common herniation level is L4-L5, 95% rupture occurs at this levels. Almost 90% patients are relieved symptomatically with conservative treatment within 3 months period. There are various surgical methods if conservative treatment fails. The operative techniques are Open discectomy, microscopic discectomy, Standard microdiscectomy, endoscopic discectomy. The most commonly performed surgical procedure is standard microdiscectomy. METHODOLOGY: This is retrospective study of open lumbar microdiscectomy done at Shree Birendra Hospital from 2013 to 2018.The inclusion criteria are age <45yrs,presence of radicular feature, failure of conservative treatment. In all patients leg and back pain, neurological involvement were recorded pre and post operative. The data were analysed in SPSS 21. RESULTS: There were 123 cases and 20 cases were lost for follow up. There were 93 male patients out of 103. The age range was between 23 to 69 yrs and mean age was 36.4± 9.5 yrs. 53 patients had left sided herniation and rest had right sided and central. 85 patients had clinical and neurological improvement. Eight patients had back pain and developed discitis, one had incidental durotomy and one wrong diagnosis. Out of eight discitis, 6 patients relieved with conservative treatment in 6 months period and two had TLIF surgery. CONCLUSION: There are various surgical option for lumbar disc prolapse if conservative management fails. Standard open microdiscectomy is cost effective, less technical demanding and has effective clinical outcome.